Fixture for High-Frequency Viscoelastic Transfer Path Analysis in Application to Elastomer Sealing Rings in Electric Motors - Michael Schnell; Marvin Gradtke; Frank Gauterin (Vibration, 2021)
In this paper, the frequency response functions of rubber o-rings are investigated. A growing trend is the application of electric motors in vehicle powertrains. Electric motors exhibit a different kind of structural dynamic excitation, compared to conventional internal combustion engines. Especially the excitation frequency is multiple times higher, as in combustion engines. This increased excitation frequency is a novel requirement on materials and their modelling in simulations. For this case, a novel fixture is introduced, which constrains the rubber o-ring components in their designated conditions and which allows to perform a Transfer-Path-Analysis up to a frequency of 6.5 kHz. The evaluation of the results shows a high coherence throughout the considered frequency range, while using a high-frequency miniature shaker. The structural resonances are clearly visible and the signal noise is low. This proves the suitability of the presented fixture, in combination with the high-frequency miniature shaker. The results presented and the fixture itself serve as a basis for further work and developments.